Group Harmony : The Black Urban Roots of Rhythm and Blues - Goosman, Stuart L., 1953-2017 (Book collections on Project MUSE., 2005)
Drawing on dozens of interviews with performers, deejays, and industry professionals, Group Harmony details the emergence of vocal rhythm & blues out of black urban neighborhoods in the postwar period.